Carbonization of Palm Oil Empty Fruit Bunch (EFB) in Hydrothermal Processes to Produce Biochar - Rakhman Sarwono; Silvester Tursiloadi; Kiky Corneliasari Sembiring (Jurnal Kimia Terapan Indonesia, 2016)
ABSTRACT Empty fruit bunch (EFB) of palm oil is a waste from the palm oil industries which in a large amount, those waste is not properly utilized yet.  EFB is a lignocelluloses waste as a polymer with big molecule such as cellulose, lignin, and hemicelluloses that can be degraded into smaller molecules in hydrothermal carbonization (HTC) process. The HTC process of EFB will result three fractions such as gas, organic water soluble and biochar as solid residue or bio-char-water-slurry. EFB degradation is influenced by the operation conditions such as temperature, pressure, catalysts, reaction time, stirring and ratio liquid and solid. The HTC  process involved many routes of reaction such as liquefaction, hydrolysis, dehydration, decarboxylation, condensation, aromatization, and polymerization. In this experiment 60 ml closed vessel was used as the HTC reactor to degrade of EFB. EFB concentration of 6.44%   resulted 62%  of conversion. Reaction time of 6 hours resulted    62 % of conversion. Increasing the reaction time and temperature increase the conversion  of  EFB. Liquid products of organic water soluble has cleared  yellow color, after several hours the color become darkness that is further reaction still occurs in that solution.  Solid products is biochar  as brown coal,  that can be easily separated and processed into powder, pellet or briquette form with outstanding storage and transport characteristics. For further economic development, biochar with excellent transport characteristics, the possibility of exporting this commodity to the world’s energy market is possible.   Key words: EFB, hydrothermal, carbonization, conversion, biochar